Haemochromatosis in children: A national retrospective cohort promoted by the A.I.E.O.P. (Associazione Italiana Emato‐Oncologia Pediatrica) study group - Corti, Paola; Ferrari, Giulia Maria; Faraguna, Martha Caterina; Capitoli, Giulia; Longo, Filomena; Corradini, Elena; Casini, Tommaso; Boscarol, Gianluca; Pinto, Valeria Maria; Ghilardi, Roberta; Russo, Giovanna; Colombatti, Raffaella; et al. (British journal of haematology, 2024)
Haemochromatosis (HC) encompasses a range of genetic disorders. HFE‐HC is by far the most common in adults, while non‐HFE types are rare due to mutations of HJV , HAMP, TFR2 and gain‐of‐function mutations of SLC40A1 . HC is often unknown to paediatricians as it is usually asymptomatic in childhood. We report clinical and biochemical data from 24 paediatric cases of HC (10 cases of HFE‐, 5 TFR2‐, 9 HJV‐HC), with a median follow‐up of 9.6 years. Unlike in the adult population, non‐HFE‐HC constitutes 58% (14/24) of the population in our series. Transferrin saturation was significantly higher in TFR2‐ and HJV‐HC compared to HFE‐HC, and serum ferritin and LIC were higher in HJV‐HC compared to TFR2‐ and HFE‐HC. Most HFE‐HC subjects had relatively low ferritin and LIC at the time of diagnosis, so therapy could be postponed for most of them after the age of 18. Our results confirm that HJV‐HC is a severe form already in childhood, emphasizing the importance of early diagnosis and treatment to avoid the development of organ damage and reduce morbidity and mortality. Although phlebotomies were tolerated by most patients, oral iron chelators could be a valid option in early‐onset HC.